Perancangan Sistem Inventaris Kitchen Untuk Meningkatkan Efisiensi Operasional Menggunakan Metode Waterfall Pada Pt. Bakerindo Sukses Makmur - Kahfi Djaelani Setiawan, Ahmad; Chandra Dewi, Helen; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Efficient inventory management is a key factor in ensuring smooth operational processes within a company. This report discusses the design of a web-based inventory system using the Waterfall method at PT. Bakerindo Sukses Makmur, aiming to enhance the company's operational efficiency. The system is designed to address the limitations of manual processes, which often lead to recording errors, overstocking, or stock shortages.The Waterfall method was chosen for its structured and systematic approach to system design and development. The designed system includes features such as automatic stock recording, real-time inventory reports, and the ability to generate reports in PDF format. The implementation of this system demonstrates a positive impact on inventory management efficiency, speeds up decision-making processes, and improves data accuracy. Testing was conducted using the black box testing method, showing that all features functioned as required. This system provides an effective digital solution to support the company’s inventory management and is expected to be further developed with enhanced security features and broader data integration in the future.